2016
DOI: 10.1177/2048872616633850
|View full text |Cite
|
Sign up to set email alerts
|

Coronary flow improvement following unsuccessful primary percutaneous coronary intervention in ST-elevation myocardial infarction with diffuse ectatic coronary artery

Abstract: In patients with STEMI in giant coronary artery with diffuse ectasia, achievement of TIMI grade 3 flow was significantly reduced immediately after percutaneous coronary intervention. However, improvement of coronary flow up to TIMI grade 3 was not uncommon at follow-up angiogram. Patients had low mortality despite low TIMI grade 3 achievement immediately after primary percutaneous coronary intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…16 However, these findings were limited by the unadjusted statistical analysis, the relatively small sample size, the paucity of adverse events, and the short-term follow-up time. Fujii et al 26 documented a crude value of lower mortality in CAE patients compared to no CAE at 1 year after STEMI. However, the propensity-matched analysis between groups did not detect any statistically significant difference, confirming the hypothesis that these findings could be the result of different baseline characteristics between the two populations.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, these findings were limited by the unadjusted statistical analysis, the relatively small sample size, the paucity of adverse events, and the short-term follow-up time. Fujii et al 26 documented a crude value of lower mortality in CAE patients compared to no CAE at 1 year after STEMI. However, the propensity-matched analysis between groups did not detect any statistically significant difference, confirming the hypothesis that these findings could be the result of different baseline characteristics between the two populations.…”
Section: Discussionmentioning
confidence: 99%
“…e results revealed that the implementation of percutaneous coronary intervention after drug thrombolysis can effectively reduce the blood flow patency time, thereby restoring myocardial blood perfusion and effectively protecting cardiac function. Compared with group A, the pre-proBNP content in groups B and C was significantly lower at 1 week, 2 weeks, and 3 weeks after treatment and significantly lower in group C than in group B (P < 0.05); the study found that atrial fibrillation, arrhythmia, pulmonary hypertension, asthma, pneumonia, and other diseases could cause abnormal increase of pre-proBNP [23], that is, the decrease of proBNP content could reflect that the patient's cardiac function was improved to a certain extent.…”
Section: Discussionmentioning
confidence: 67%
“…In only 50% of the patients with diffuse ectatic coronary arteries a TIMI grade 3 flow is achieved immediately after primary PCI for STEMI. 7 Many of these patients however show a normalisation of the epicardial coronary flow during the chronic phase and the mortality is much lower than expected on the basis of the high prevalence of a TIMI grade 2 or less flow. It is speculated that the intracoronary thrombus in these patients may have a different composition since it is formed due to flow sluggishness in ectacic coronary arteries.…”
mentioning
confidence: 94%